Analisis Interaksi Pembangunan Manusia Dan Pertumbuhan Ekonomi Antara Kabupaten Dan Kota Di Sumatera Barat - Annisa Eka Putri; Hasdi Aimon; Hari Setia Putra (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to analyze the effect of poverty, unemployment, investment, and government expenditure on human development (health and education) and economic growth, as well as analyze the relationship between human development (education and health) and economic growth in districts and cities of the province of West Sumatra. The data used is panel data consisting of a cross section of 7 districts and 7 cities in West Sumatra Province and time series from 2015 - 2020. This study uses a simultaneous model (2sls). The results of this study that human development (education) is influenced by unemployment in the district, while in the city, poverty, unemployment, economic growth have not had an impact on human development (education and health). On the other hand, economic growth in the district is influenced by government expenditure, while in the city, investment, government expenditure and human development (education and health) have not had an impact on economic growth. From the econometrics study, it is found that human development (education and health) and economic growth have not had a mutually influencing impact or there is no causal relationship either in the district or in the city. We conclude that the government needs to improve human development in the fields of education and health and economic development in order to make a good contribution to the development of a region.